Catalytic effects of MgFe2O4 addition on the dehydrogenation properties of LiAlH4. (25th October 2019) - Ali, N.A.; Idris, N.H.; Sazelee, N.A.; Yahya, M.S.; Yap, F.A. Halim; Ismail, M.
Abstract: Study on the catalytic roles of MgFe2 O4 on the dehydrogenation performance of LiAlH4 was carried out for the first time. Notable improvement on the dehydrogenation of LiAlH4 –MgFe2 O4 compound was observed. The initial decomposition temperatures for the catalyzed LiAlH4 were decreased to 95 °C and 145 °C for the first and second stage reactions, which were 48 °C and 28 °C lower than the milled LiAlH4 . As for the desorption kinetics performance, the MgFe2 O4 doped-LiAlH4 sample was able to desorb faster with a value of 3.5 wt% of hydrogen in 30 min (90 °C) while the undoped LiAlH4 was only able to desorb 0.1 wt% of hydrogen. The activation energy determined from the Kissinger analysis for the first two desorption reactions were 73 kJ/mol and 97 kJ/mol; which were 31 and 17 kJ/mol lower as compared to the milled LiAlH4 . The X-ray diffraction result suggested that the MgFe2 O4 had promoted significant improvements by reducing the LiAlH4 decomposition temperature and faster desorption kinetics through the formation of active species of Fe, LiFeO2 and MgO that were formed during the heating process. Highlights: The H2 storage properties of LiAlH4 /MgFe2 O4 have been studied for the first time. Desorption properties of LiAlH4 are improved after adding with MgFe2 O4 . LiAlH4 //MgFe2 O4 composite could desorb 3.5 wt% H2 within 30 min at 90 °C. The formation of new species of Fe, LiFeO2 and MgO phases plays a catalytic role.